Narcotrafficking and Land Control in Guatemala and Honduras. Issue 1 (4th October 2021) - Tellman, Beth; McSweeney, Kendra; Manak, Leah; Devine, Jennifer A.; Sesnie, Steven; Nielsen, Erik; Dávila, Anayansi
On frontiers dominated by illicit activities such as narcotrafficking, criminal organizations' usurpation of land and resources is profoundly changing rural livelihoods and prospects for biodiversity conservation. Prior work has demonstrated how drug trafficking catalyzes forest loss and smallholder dispossession but does not make clear the extent to which the long-term control of land is moved from state, Indigenous, or smallholders to criminal or other actors. This study attempts to describe those shifts. Specifically: we develop a typology of land control, and use it to track how drug trafficking initiates shifts from public lands and Indigenous territories to private large holdings. We examine an array of secondary sources indicating shifts in land control related to narcotrafficking, including illegal land seizure documents, news media, and surveys of land managers. In absence of formal land registries, frontier actors may signal their control over land through land use change. After establishing where changes in land control have taken place, we analyzed land use and resulting changes in spatial patterns of forest loss. We found that large scale sustained forest losses (over 713, 244 ha and 417, 329 ha), in Guatemala and Honduras, respectively, from 2000–2019) corresponds with areas undergoing shifts in control towards large landowners, often related to narcotrafficking. Incomplete empirical data on land control prevent comprehensive attribution of all sustained forest loss related to narcotrafficking. Yet the limited evidence gathered here indicates drug trafficking activities initiate widespread and sustained shifts and consolidation of who controls land and resources at the frontier. Our work suggests that in Central America and likely elsewhere, control over land—quite separate from property rights —is the key factor in understanding social and ecological change.